The complete chloroplast genome sequence of medicinal plant: Astragalus laxmannii (Fabaceae) - Yi Liu; Yang Chen; Xi Fu (Mitochondrial DNA. Part B. Resources, 2020)
Astragalus laxmannii is a traditional Chinese medicine. The complete chloroplast genome sequence is 122,844 bp in length, contains 110 complete genes, including 75 protein-coding genes (75 PCGs), 8 ribosomal RNA genes (4 rRNAs), and 30 tRNA genes (30 tRNAs). The overall GC content of cp DNA is 34.1%. Phylogenetic tree shows that A. laxmannii is a sister to A. strictus.